2020
DOI: 10.4103/1673-5374.276337
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic exercise program-modulated oxidative stress markers in patients with Parkinson's disease

Abstract: Parkinson’s disease is a neurodegenerative disease. Oxidative stress, i.e., the imbalance between the generation of reactive oxygen species and the antioxidant defense capacity of the body, plays an important role in the pathogenesis of this disease. Physical exercise can regulate oxidative stress. The purpose of this study was to analyze the short- and long-term effects of an aquatic exercise program on oxidative stress levels in patients with Parkinson’s disease. The aquatic exercise program was carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Previous studies have confirmed that aquatic exercises can more effectively control posture and maintain balance (Becker, 2009;Zhang et al, 2016;Zhu et al, 2018). 2) The warming effect of water can stimulate temperature receptors and activate cortical sensory-related areas, regulate oxidative stress, increase the reaction between nerves and hippocampus (Silva Germanos et al, 2019;Dani et al, 2020), increase the activity of cortical sensory and motor areas, and promote sensorimotor integration. It also increases the extensibility of collagen tissue (Ardıç et al, 2007), inhibits the over-excitability of the stretch reflex, improves the flexibility of muscle function, relieves stiffness, and increases the self-confidence and training enthusiasm of patients.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have confirmed that aquatic exercises can more effectively control posture and maintain balance (Becker, 2009;Zhang et al, 2016;Zhu et al, 2018). 2) The warming effect of water can stimulate temperature receptors and activate cortical sensory-related areas, regulate oxidative stress, increase the reaction between nerves and hippocampus (Silva Germanos et al, 2019;Dani et al, 2020), increase the activity of cortical sensory and motor areas, and promote sensorimotor integration. It also increases the extensibility of collagen tissue (Ardıç et al, 2007), inhibits the over-excitability of the stretch reflex, improves the flexibility of muscle function, relieves stiffness, and increases the self-confidence and training enthusiasm of patients.…”
Section: Discussionmentioning
confidence: 96%
“…Exercise is an effective remedy against a wide range of aging processes. Exercise modulates the oxidative stress axis, potentially slowing and improving chronic kidney failure, Parkinson's disease, Alzheimer's disease, muscle aging, and aging‐induced vascular dysfunction 18–20 . In the brain, moderate exercise ameliorates oxidative stress‐induced neuroinflammation and neuronal apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the endocannabinoid system becomes activated under parabolic flight ( Strewe et al, 2012 ), and such hormones, as adrenocorticotropic hormone (ACTH) and cortisol, are increased under parabolic or spaceflight ( Schneider et al, 2007 ). In PD subjects, water immersion in combination with exercises was reported to decrease the concentration of serum cytokines, thus exerting anti-inflammatory ( Pochmann et al, 2018 ) and pro-antioxidative effects ( Dani et al, 2020 ). In healthy people, brain-derived growth factor is increased after water immersion ( Kojima et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%